Two notes on Rafał Kubiak article (Diametros, 2023)
The following text is a voice in the discussion around normative problems of innovative therapies. It particularly refers to the amendment to the Polish Act on the Professions of Physician and Dentist, also discussed in this issue in the article by Rafał Kubiak "Criminal liability for crimes related to the illegal conduct of a medical experiment."
Keywords: medical experiments; participant’s consent; (medical) law